Screening three cultivars of mutant Potato with sodium azide for salt tolerance - Hussain, L.A; Al-Miahy,Falah H (University of Thi-Qar Journal of agricultural research, 2022)
In vitro non- mutated and mutated plants with sodium azide at a concentration of 1 m mol for 30 minutes of three cultivars of Potato (Arnova, Provento and Emma) were screened to salt tolerate. Plants cultured in MS medium supplimented with different levels of sodium chloride (8, 10, 12 and 14 ds m-1) with comparison treatment ( electrical conductivity 6 ds m-1). The cultures were incubated at a temperature of 25 ± 2 and 16 hours day -1. The data were taken on the morphological characteristics of the vegetative growth (plant height, number of shoots and nodes) and the fresh weight of the vegetative group and its content of Na+, K+, Ca++ and amino acid proline. The results showed that the cultivars differed significantly in the morphological characteristics (plant height, number of nodes and the fresh weight of the vegetative growth, Arnova cultivar superior with rates 5.55 cm, 5.72 plant node plant-1 and 236 mg, respectively. Salinity also caused a decrease in the rates of these traits by increasing the salinity levels in addition to its effect in increasing the accumulation of Na+ and decreasing K+, while it had no significant effect on the accumulation of Ca++ and the amino acid proline. Mutation had no significant effect on the accumulation of Ca++ and proline, while an increase K+ in Provento cultivar at all salinity levels compared to 6 ds m-1 and a decrease in the Na+ content at 6, 8 and 14 ds. m-1.